Desenvolvimento industrial em espaços organizados: uma análise dos fatores de competitividade nos distritos industriais do Estado do Rio de Janeiro - Gurgel, Alexandre Castanhola (2015)
Industrial development in the Organized Space (OS) has been given through public policies and private initiatives, bearing in mind, in some cases, to competitiveness factors for their respective implementation, other times not so much. The main objective of this study was to analyze the factors of competitiveness of the industrial districts of the State of Rio de Janeiro, contributing in this way by the results presented at the end of the work, to support new public policies and / or support to private initiatives, when the attraction, deployment, retention and expansion of industries and related businesses in these areas. The delimitation of the sample of Organized Spaces (OSs) was contingent on the availability of data and homogeneity of the sample, in this case, industrial districts in the state of Rio de Janeiro. In carrying out the stages of the project to achieve its main goal, intermediate steps were carried out as follows: Nomenclature of identification available for the types of OSs; preparation of proposal for the characterization of OSs; identifying competitiveness factors of existing OSs in the state of Rio de Janeiro; validation of competitiveness factors with the group interviewed government officials, municipalities, development agencies and executives of companies operating in the studied areas; mapping of existing OSs in the state of Rio de Janeiro and analysis of these spaces competitive factors, with their correlations as creating jobs and attracting businesses. Finally, after analyzing the results, discussion and closing remarks showed trends that can be deepened in future support efforts to prepare the public and / or private strategies aimed at better utilization and use of OSs for the industrial development.